Kajian Teoretik Penelitian Khotbah - Andreas Rudy Hartono (Sekolah Tinggi Teologi Blessing Indonesia Makassar, 2022)
The essence of the sermon must be interpreted in terms of the true meaning and understanding of the sermon itself. The contents of the sermon may go hand in hand with the discrepancy with the true meaning of the sermon. This needs to be criticized theologically and practically so that anyone who delivers a sermon cannot be separated from the truth that has been standardized in God's Word. In the development of science and technology, the